Design and Optimization of a New Type of the Back Pressure Reducing Back-lifting Mechanism - Pan Ao; Yu Chengtao; Sun Xuebin; Huang Guangming; Zhou Xiangyu (Jixie chuandong)
In order to solve the problem of back pressure caused by the nursing bed during the back lifting process, a new type of back lifting mechanism that can link with the waist plate is innovatively designed. Firstly, the multi-link mechanism is used to realize the linkage of the waist plate during the back lifting process, and the triangular suspended area generated in the waist part during the back lifting process is filled, so as to provide support to the waist and reduce the back pressure. When the back is lifted, the raised waist plate acts as a cushion, which is more in line with the ergonomic requirements under the sitting state. Combined with the parameters of the body size, the back forces of the new back lifting mechanism and the traditional back lifting mechanism are analyzed and compared, and it is verified that the new back lifting mechanism can reduce the back pressure feeling. In addition, the kinematics analysis of the back lifting mechanism is executed, and the parametric modeling is carried out. Meanwhile, the size optimization design is carried out with the minimization of the maximal angular acceleration of the back plate as the optimization objective. Then, the dynamic simulation of the mechanism is carried out to obtain the maximum force in the movement process, which is imported into Ansys for statics simulation to verify the safety and stability of the back lifting mechanism. Finally, a prototype testing is conducted to verify the lifting angle of the back plate and the smoothness during the lifting process through an angle sensor.